If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t = 2t + -51 Reorder the terms: t = -51 + 2t Solving t = -51 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. t + -2t = -51 + 2t + -2t Combine like terms: t + -2t = -1t -1t = -51 + 2t + -2t Combine like terms: 2t + -2t = 0 -1t = -51 + 0 -1t = -51 Divide each side by '-1'. t = 51 Simplifying t = 51
| 3y=-x-2 | | 4y-5x=4y-5x | | 8/9-5/6×1/3 | | 4b+64=2b+68 | | 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y | | 3q+6=6q | | 3+3(2-6)= | | -5+6x=x+10 | | 2s-48=s | | 2s+40=4s+28 | | x/3-=11 | | 3y=7x-9 | | 9x-12y+6=0 | | 3s-62=s | | 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 |